Use of Kisser glycerol gelatin to prepare microscope slides of Phlebotomine sandflies (Diptera: Psychodidae) - Vanusa Gonçalves Holanda; Diogo Brunno e Silva Barbosa; Leudimar Aires Pereira; Maria Regiane Araujo Soares (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: Appropriate preservation of specimens is important for taxonomic identification. In sandfly research, various methods have been used for slide preparation; however, high cost, low commercial availability, and associated hazards make their use impossible in some studies. Therefore, the efficacy of Kisser glycerol gelatin for sandfly slide preparation was tested. METHODS: Kisser glycerol gelatin, as a substitute for Canada balsam and Berlese’s fluid, was used for mounting sandflies. RESULTS: Forty-two mounted specimens were created and maintained even after 14 months. CONCLUSIONS: Use of Kisser glycerol gelatin is simple and efficient for preparing microscope slides of sandflies.